Foreign body aspirations in dental clinics: a narrative review - Huh, Jin-Young (Journal of Dental Anesthesia and Pain Medicine, 2022)
Foreign body aspiration can produce a medical emergency. Obstruction of the airways can be life-threatening, and complications may develop in less-severe cases if it is left untreated. Although it is more prevalent in children by approximately three times, adults can still experience it, and it is more frequently related to healthcare in adults. Objects used in dental treatment are usually placed in the oral cavity and can be ingested or inhaled by accident. Dental treatment has been identified as an important cause of the misplacement of foreign bodies in the airway. However, few reports have been published on dentistry-related foreign body aspiration. This paper discusses the disease course, management, and clinical outcomes of foreign body aspiration, especially those associated with dentistry. The patient must be examined for respiratory distress. If the patient is unstable, urgent airway management and the maneuvers for removal should be performed. Radiographs and computed tomography can help identify and locate the object. The treatment of choice is often bronchoscopy, and both flexible and rigid endoscopes can be used depending on the situation. Preventive measures need to be implemented to avoid inhalation accidents given the potential consequences. Though the incidence is rare, healthcare levels need to be enhanced to avert morbidity and mortality. Radiological evaluation and bronchoscopy are vital for management.